Massively multiplayer online role-play games for learning - de Freitas, Sara; Griffiths, M. (IGI Global, 2009)
This chapter explores whether massively multiplayer online role-play games (MMORPGs) can be usedeffectively to support learning and training communities. The chapter aims to propose that cross-disciplinaryapproaches to the study of game-based learning are needed to support better synthesis ofour current understanding of the effectiveness of learning with games. The chapter therefore includesa brief literature review of online gaming research to date, taken from psychological and educationalresearch perspectives. The chapter explores the main types of online games and highlights the mainthemes of research undertaken through a consideration of the use of online gaming in current learningand training contexts where online gaming is being used to support experiential and discovery learningapproaches. This chapter indicates future directions for cross-disciplinary research approaches in thisfield and considers how collaborative learning could best be supported through this approach.